Production of Lipase Enzyme by Marine Actinobacteria With Various pH and Temperature - Aulia, Muhammad Rizqi; Agustriana, Eva; Fitri, Lenni (Elkawnie: Journal of Islamic Science and Technology, 2024)
Abstract: The demand for enzymes as biocatalysts in industry is very high. Research and development of different types of enzymes from different sources has started. One very important enzyme to study is the enzyme lipase. Lipase enzymes are enzymes of the hydrolase class that catalyze the hydrolysis of triglycerides to glycerol and free fatty acids. Lipases are found in a variety of sources including animals, plants, and microorganisms. Marine microorganisms, including marine actinobacteria, cannot be separated from this enzyme source's research and development process. The purpose of this study was to obtain a test protocol and optimal pH and temperature conditions for the hydrolysis reaction by lipase enzymes from marine actinobacteria. Optimal pH and temperature conditions for hydrolysis reactions by lipase enzymes from marine actinobacteria using spectrophotometry at different pH values and different temperatures of 3, 4, 5, 6, 7, 8, 9, and 10. Temperatures of 30 °C, 40 °C, 50 °C, 60 °C, 70 °C, 80 °C and 90 °C are measured at a wavelength of 405 nm. The results showed that the activity of the lipase enzyme at pH 9 with Tris-HCl buffer was the optimum pH, and the temperature of 70°C was the optimum temperature for the lipase hydrolysis reaction of marine actinobacteria.Abstrak: Kebutuhan enzim sebagai biokatalisator dalam bidang industri sangat tinggi. Berbagai macam enzim dari beragam sumber sudah mulai diteliti dan dikembangkan. Salah satu enzim yang sangat penting untuk diteliti adalah enzim lipase. Enzim lipase merupakan enzim golongan hidrolase yang mengkatalis proses hidrolisis trigliserida menjadi gliserol dan asam lemak bebas. Lipase dapat ditemukan dalam berbagai sumber seperti pada hewan, tumbuhan, dan mikroorganisme. Mikroorganisme laut tidak terlepas dari proses penelitian dan pengembangan sumber enzim ini termasuk Actinobacteria laut. Tujuan penelitian ini adalah untuk memperoleh protokol uji dan kondisi pH dan temperatur optimum reaksi hidrolisis oleh enzim lipase dari Actinobacteria laut. Kondisi pH dan temperatur optimum reaksi hidrolisis oleh enzim lipase dari Actinobacteria laut dilakukan secara kuantitatif dengan metode spektrofotometri pada variasi pH 3, 4, 5, 6, 7, 8, 9, dan 10 dan variasi suhu 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, dan 90°C diukur pada Panjang gelombang 405 nm. Hasil menunjukkan bahwa aktivitas enzim lipase pada pH 9 menggunakan buffer Tris HCl merupakan pH optimum dan temperatur 70°C merupakan temperature optimum reaksi hidrolisis enzim lipase dari Actinobacteria laut.